Filippo Mazzei papers - Mazzei, Filippo, 1730-1816.
Chiefly correspondence with John Adams, Thomas Jefferson, Marquis de Lafayette, James Monroe, and Edmund Randolph. The largest group of letters is from Thomas Jefferson and includes the "Mazzei letter" (1796 April 24), in which Jefferson criticizes Federalist leaders.
Italian physician and merchant and colonial American agent in Europe.
Collection material in English, with French and Italian.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Adams, John, -- 1735-1826 -- Correspondence; Lafayette, Marie Joseph Paul Yves Roch Gilbert du Motier, -- marquis de, -- 1757-1834 -- Correspondence; Jefferson, Thomas, -- 1743-1826 -- Correspondence; Monroe, James, -- 1758-1831 -- Correspondence; Randolph, Edmund, -- 1753-1813 -- Correspondence; Federal Party (U.S.); Europe -- Foreign relations -- United States; United States -- Foreign relations -- Europe; Colonial agents; Merchants -- Italy; Physicians